Acidic cellular microenvironment modifies carcinogen-induced DNA damage and repair - Shi, Q. (Arch Toxicol, 2016)
Chronic inflammation creates an acidic microenvironment, which plays an important role in cancer development. To investigate how low pH changes the cellular response to the carcinogen benzo[a]pyrene (B[a]P), we incubated human pulmonary epithelial cells (A549 and BEAS-2B) with nontoxic doses of B[a]P using culturing media of various pH’s (extracellular pH (pH(e)) of 7.8, 7.0, 6.5, 6.0 and 5.5) for 6, 24 and 48 h. In most incubations (pH(e) 7.0–6.5), the pH in the medium returned to the physiological pH 7.8 after 48 h, but at the lowest pH (pH(e) < 6.0), this recovery was incomplete. Similar changes were observed for the intracellular pH (pH(i)). We observed that acidic conditions delayed B[a]P metabolism and at t = 48 h, and the concentration of unmetabolized extracellular B[a]P and B[a]P-7,8-diol was significantly higher in acidic samples than under normal physiological conditions (pH(e) 7.8) for both cell lines. Cytochrome P450 (CYP1A1/CYP1B1) expression and its activity (ethoxyresorufin-O-deethylase activity) were repressed at low pH(e) after 6 and 24 h, but were significantly higher at t = 48 h. In addition, a DNA repair assay showed that the incision activity was ~80% inhibited for 6 h at low pH(e) and concomitant exposure to B[a]P. However, at t = 48 h, the incision activity recovered to more than 100% of the initial activity observed at neutral pH(e). After 48 h, higher B[a]P-DNA adduct levels and γ-H2AX foci were observed at low pH samples than at pH(e) 7.8. In conclusion, acidic pH delayed the metabolism of B[a]P and inhibited DNA repair, ultimately leading to increased B[a]P-induced DNA damage. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00204-016-1907-4) contains supplementary material, which is available to authorized users.